2022
DOI: 10.1038/s41598-022-20655-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biochemical assessment of mixture effects of two endocrine disruptors on INS-1 cells

Abstract: Abstract4-tert-Octylphenol (4-tOP) is a component of non-ionic surfactants alkylphenol polyethoxylates while triclosan (TCS) is an antibacterial present in personal care products. Both compounds can co-exist in environmental matrices such as soil and water. The mixture effects of these micropollutants in vitro remains unknown. INS-1 cells were exposed to 20 µM or 30 µM 4-tOP and 8 µM or 12.5 µM TCS as well as equimolar mixture of the chemicals (Mix) in total concentration of 12.5 µM or 25 µM for 48 h. Mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This meant that in glutamate metabolism that was affected by ME, the synthesised L ‐glutamic acid may be more inclined to participate in the formation of glutathione (GSH) along with L ‐cysteine. It has been reported that GSH is an important endogenous antioxidant substance which is involved in catalytic cycles of antioxidant enzymes such as glutathione peroxidase (GSH‐Px) (Olaniyan & Okoh, 2022). Interestingly, this speculation is further supported by our previously published results in piglets where ME treatment significantly improved the enzyme activity of GSH‐Px compared to its control (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This meant that in glutamate metabolism that was affected by ME, the synthesised L ‐glutamic acid may be more inclined to participate in the formation of glutathione (GSH) along with L ‐cysteine. It has been reported that GSH is an important endogenous antioxidant substance which is involved in catalytic cycles of antioxidant enzymes such as glutathione peroxidase (GSH‐Px) (Olaniyan & Okoh, 2022). Interestingly, this speculation is further supported by our previously published results in piglets where ME treatment significantly improved the enzyme activity of GSH‐Px compared to its control (Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%